Analysis of the Development Trend of Electric Power Technology - Zhu, Shufan; Zhu, Rongyan (Journal of Theory and Practice of Engineering Science, 2023)
After decades of reform and opening up, China's development structure is constantly upgrading, and the quality of development is also constantly improving. As one of the main sources of clean energy, electric energy plays a vital role in people's production and life. Therefore, how to better serve all aspects of the society with power production technology is the current development must pay attention to the topic. This paper focuses on the analysis of the current situation of electric power production technology and its future development trend. Therefore, under the circumstances that logistics resources are limited and logistics activities are increasingly dependent on the market and industrial structure, Henan Province should scientifically plan and rationally allocate and use logistics resources in implementation of "One Belt, One Road" strategy to achieve the best input and output, improve the overall efficiency and level of logistics; vigorously develop local economy from the perspective of system coordination, realize coordination among logistics enterprises, logistics industry coordination, as well as inter-industry coordination and regional coordination.